Reconceptualize tall-cell variant papillary thyroid microcarcinoma: From a “sonographic histology” perspective - Zhang, Yongyue; Mei, Fang; He, Xiaoxi; Ma, Jing; Wang, Shumin (Frontiers in Endocrinology, 2022)
Objective: To explore the relationship between sonographic features and histological manifestations in tall cell variant (TCV)-papillary thyroid microcarcinoma (PTMC), thus to propose the concept of “Sonographic Histology” and explore the value of it in clinical management of aggressive TCV. Methods: This study retrospectively included 104 participants who were admitted to Peking University Third Hospital from 2015 to 2022 and were histopathologically confirmed as TCV-PTMC or classical-PTMC. We mainly compared the general situation, sonographic characteristics, and pathological specimens in the two cohorts. Results: Hypoechoic nodules with localized central isoechoic lesion and hypoechoic halo around nodules are most often seen in TCV-PTMCs, which correlates with circumferentially distributed tumor epithelialum and densely distributed tumor stroma histopathologically. Besides, TCV-PTMCs demonstrated nodules with more regular margin and less microcalcification than classical-PTMCs, which leads to an underestimation of the risk of TCV-microcarcinomas. Conclusion: The excellent correspondence between ultrasound echo pattern and tissue cell arrangement is defined as “Sonographic Histology” in this study and applied in preoperative identification of TCV-PTMC. We suggest this concept may provide novel insights for the identification of special subtypes thyroid tumor and modify pitfalls of thyroid imaging reporting and data system (TI-RADS) in aggressive variants microcarcinoma.